Optical frequency comb generation based on chirping of Mach-Zehnder modulators - Hmood, J.K.; Emami, S.D.; Noordin, K.A.; Ahmad, Harith; Harun, Sulaiman Wadi; Shalaby, H.M.H. (Optics Communications, 2015)
A new approach for the generation of an optical frequency comb, based on chirping of modulators, is proposed and numerically demonstrated. The setup includes two cascaded Mach-Zehnder Modulators (MZMs), a sinusoidal wave oscillator, and an electrical time delay. The first MZM is driven directly by a sinusoidal wave, while the second MZM is driven by a delayed replica of the sinusoidal wave. A mathematical model of the proposed system is formulated and modeled using the Matlab software. It is shown that the number of the frequency lines is directly proportional to the chirp factor. In order to achieve the highest number of frequency comb lines with the best flatness, the time delay between the driving voltages of the two MZMs is optimized. Our results reveal that at least 51 frequency lines can be observed at the output spectrum. In addition, 27 of these lines have power fluctuations of less than 1 dB. The performance of the proposed system is also simulated using a split-step numerical analysis. An optical frequency comb, with tunable frequency spacing ranging from 5 to 40 GHz, is successfully generated. (C) 2015 Elsevier B.V. All rights reserved.